POLICY CAPACITY PADA SEKTOR OPERASIONAL KEPOLISIAN RESOR UNTUK PENGENDALIAN PENYALAHGUNAAN NARKOBA DI KABUPATEN KOTAWARINGIN TIMUR - Bimantara Nur Alim; Farlian Ansyari (UPT Publikasi Dan Pengelolaan Jurnal Universitas Islam Kalimantan MAB Banjarmasin, 2025)
The purpose of this study is to describe the policy capacity in the operational sector of the Resort Police to control drug abuse in East Kotawaringin Regency. The research refers to the implementation scope by using the theory of policy capacity in the operational sector at the individual, organizational, and system levels. This study uses a qualitative method with a descriptive type. The research was conducted in 2022 at the Resort Police in East Kotawaringin Regency with data collection techniques sourced from primary data in the form of in-depth interviews with the Narcotics Investigation Unit and secondary data sourced from the media. The results showed several indicators running well, namely operational capacity at the individual and organizational levels. On the other hand, the operational capacity of policies at the system level has not run optimally. The police try to coordinate with local governments, communities, and other institutions. However, coordination between institutions is not going well, as one of which makes coordination difficult because there is no definitive institution, namely the Regency National Narcotics Agency, which is the axis for drug control.